Examining the meanings and essentials of perfection and perfection in Islamic mysticism Community Verified icon - Reza Hesari; Hassan Ramezani; Mohammad Mahmoud Khalfan (حکمت اسرا, 2025)
Among the terms that have always been the focus of divine mystics throughout the history of Islamic mysticism, are the two terms of perfection and perfection. Although some of its roots and similar meanings can be found in religious texts, it can be said that the originators of these two terms were mystics. Sadr al-Din Qonavi is one of the mystics who tried to explain these two terms, and in fact, it can be said that he was the first mystic who explained it explicitly. After him, Ferghani, another follower of the school of Ibn Arabi, tried to explain these two terms in detail.He has explained the relationship between nominal perfection and inherent perfection in detail. Fanari also accepted his same analysis. In the meantime, some other divine mystics like Abdul Rahman Jami have tried to provide another interpretation and explanation of these two terms. In this article, the different approaches of the divine mystics will be explained and explained in an analytical-comparative way.